The Influence of Tax Knowledge, Taxpayer Awareness, and Fiscus Services on Individual Taxpayer Compliance in KP2KP, Gowa Regency - Agusdiwana Suarni; Nurhidayah Nurhidayah; Husnaeda Husnaeda (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine and analyze the influence of tax knowledge, taxpayer awareness, and tax authorities on individual taxpayer compliance in the KP2KP Gowa district. The research method in this thesis is descriptive statistical analysis, data quality test, classical assumption test, and hypothesis testing. The independent variables in this study are tax knowledge, taxpayer awareness, and tax authorities’ services, while the dependent variable is individual taxpayer compliance. The total population in this study, namely 25,504 individual taxpayers using the simple random sampling method, obtained 100 respondents as a sample. The types of data used are primary data and secondary data. This study proved that simultaneously tax knowledge, taxpayer awareness, and tax authorities have a significant effect on individual taxpayer compliance at KP2KP Gowa district. Partially, the variable knowledge of taxation and tax authorities affects individual taxpayer compliance at KP2KP Gowa district. Meanwhile, taxpayer awareness does not affect individual taxpayer compliance at KP2KP Gowa district.